2021
DOI: 10.1111/are.15140
|View full text |Cite
|
Sign up to set email alerts
|

Pectin and soybean meal induce stronger inflammatory responses and dysregulation of bile acid (BA) homeostasis than cellulose and cottonseed meal, respectively, in largemouth bass ( Micropterus salmoides ), which might be attributed to their BA binding capacity

Abstract: Dietary fibre (DF) is defined as 'non-digestible carbohydrates plus lignin' and includes non-starch polysaccharides (NSPs), hydrocolloids, resistant starch, resistant oligosaccharides and lignin associated with DF polysaccharides (Stephen et al., 2017). DF is not digested and absorbed by monogastric animals (Sinha et al., 2011), but can be fermented by intestinal microbiota (Miao et al., 2018).Therefore, it can regulate the structure of intestinal microbiota and improve intestinal health (Lin et al., 2020). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 94 publications
2
11
0
Order By: Relevance
“…5). This result indicated that the binding capacity of pectin to GCBAs might be stronger than that to TCBAs and then cause higher loss of GCBAs with feces (Ni et al 2021). Consistent with the higher value of GCBAs/TCBAs in the digesta, there was a signi cant decrease in the value of GCBAs/TCBAs in the liver, serum, and bile (P < 0.05, Fig.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…5). This result indicated that the binding capacity of pectin to GCBAs might be stronger than that to TCBAs and then cause higher loss of GCBAs with feces (Ni et al 2021). Consistent with the higher value of GCBAs/TCBAs in the digesta, there was a signi cant decrease in the value of GCBAs/TCBAs in the liver, serum, and bile (P < 0.05, Fig.…”
Section: Discussionmentioning
confidence: 54%
“…(3) DFs have a capacity to bind BAs, which varied among BAs (Ni et al, 2021;Suharoschi et al 2019). By binding BAs, DFs increased BA excretion with feces (Gunness et al 2016;Gunness and Gidley 2010;Thandapilly et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…5). This result indicated that the binding capacity of pectin to GCBAs might be stronger than that to TCBAs and then caused a higher loss of GCBAs with feces (Ni et al 2021). Coined with the higher value of GCBAs/TCBAs in the digesta, there was a significant decrease in the value of GCBAs/TCBAs in the liver, serum, and bile (P < 0.05, Figs.…”
Section: Discussionmentioning
confidence: 89%
“…3), suggested that the uptake ratio of PBAs from plasma into hepatocytes was low in fish fed PEC diet, which also contributed to the low PBAs in bile. (3) DFs have a capacity to bind BAs, which varied among BAs (Ni et al 2021;Suharoschi et al 2019). By binding BAs, DFs increase the BA excretion with feces (Gunness et al 2016;Gunness and Gidley 2010;Thandapilly et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Cottonseed meal (CSM) is an important plant protein source. It is widely used in feeds of different fish species, such as juvenile black sea bream ( Acanthopagrus schlegelii ) (Sun et al, 2015), juvenile black carp ( Mylopharyngodon piceus ) (Hu et al, 2015), juvenile ussuri catfish ( Pseudobagrus ussuriensis ) (Bu et al, 2017), grass carp (Hu et al, 2019), juvenile blunt snout bream ( Megalobrama amblycephala ) (Yuan et al, 2019), silver sillago ( Sillago sihama Forsskal) (Liu, Dong, et al, 2020), largemouth bass ( Micropterus salmoides ) (Ni et al, 2021) and others. However, the free gossypol contained in cottonseed meal is toxic to fish, limiting its addition in fish feed.…”
Section: Introductionmentioning
confidence: 99%